Relationships between Political Ideology and cognitive schemas about “the left” in Argentina - Brussino, Silvina (2018)
This study aims to contribute to the understanding of left-wing political ideologies from a Political Psychology perspective. We gathered data regarding ideology’s symbolic and operative aspects, and citizens’ cognitive categories about the “left in Argentina”. The sample included 495 18- to 65-year-old citizens from Cordoba (Argentina). The data was analyzed in two phases, considering a mixed method approach: 1) semantic network analysis of cognitive categories about the “left in Argentina”, 2) exploratory analysis and ANOVA.The most significant results included a rich semantic network regarding the “left in Argentina” structured into six nodes ‒negative conceptions, institutionalist left, “narrative” of the seventies, counterhegemonic classism, great principles of the left, social left. After a moderate degree of adjustment (Fitness, 375) 91% of the sample was categorized. Furthermore, the ANOVA provided data about differences between cognitive categories and ideological indicators. Finally, post hoc analysis shows that those who see “the left” in Argentina from “negative conceptions” and “narrative” of the seventies, are located further to the right while those who see it as “left institutionalist”, “ counterhegemonic classism “,”great principles of the left” and “social left” positioned further to the left.